THE STRENGTHENING SUPPORT ACCORDING TO SANGAHAWATTHUDHAMMA OF BAN LAMKAEN COMMUNITY, THAI MUEANG DISTRICT, PHANG NGA PROVINCE - Apiboonno, Phrakru Kowitbunyasan; ., Phrakru Kosolattakit; ., Phrakru Kositwattananukul; ., Phrakru Wijitsaturot; (Woratanthi), Phramaha Thanisorn Jantawanno (Journal of MCU Nakhondhat, 2024)
The objectives of this research paper are 1) Study the concepts related to the mutual support of Ban Lamkaen community, Thai Mueang District, Phang Nga Province 2) Study the principles of SangghahavatthuDhamma appearing in the Theravada Buddhist scriptures and 3) Study the strengthening mutual support according to the principles of SanghahavatthuDhamma of Ban Lamkaen Community, Thai Mueang District, Phang Nga Province. It is a qualitative research. The researcher will survey and collect data through in-depth interviews. The data will be analyzed, summarized, and presented in a descriptive writing format. The results of the research found that 1) The concept of strengthening mutual support of Ban Lamkaen community, Thai Mueang District, Phang Nga Province, was found to be an increase in the nature of helping. Helping each other out to those in trouble in the community, neighbors, and various activities related to the community. By adhering to the principles of traditional community ways, that is based on the principle of caring for each other. 2) SangghahavatthuDhamma, which appears in Theravada Buddhist scriptures, is found to be important Dhamma principle to help and support each other. It consists of 4 elements: 1) Dana, giving alms and sharing of things and all various knowledge. 2) Piyavaja, using kind and friendly speech with none being toxic to others. 3) Atthajariya, supporting and benefitting others with public mind. 4) Samanatta, proper self-positioning consistency. 3) Strengthening mutual support according to the principles of SangghahavatthuDhamma of Ban Lamkaen community, Thai Mueang District, Phang Nga Province, found that this could reduce communities’ problems, such as, the children’s problems underprivileged educational opportunities, the problem about lack of words for encouragement to each other and the problem about lack of cooperation in the community, which all can be alleviated. The conclusion of Sangghahavatthu Dhamma is a principle to reinforce and create goodwill in the community which will make a power of love and harmony, which is characteristic of a good.